Dynamic switching based real-time routing in low-duty-cycle wireless sensor networks - Quan CHEN; Hong GAO (Tongxin xuebao)
The dynamic switching based real-time(DSRT)routing protocol was proposed to handle the arbitrary end-to-end(E2E)real-time communication in the low-duty-cycle wireless sensor networks.Firstly,the concept of available speed was designed to compensate for the big sleep latency and facilitate discovering the routes with less latency based on two-hop neighbors’ information(at lease about 20% routing path with less latency was discovered by DRST in the experiments).Moreover,it was noticed that the congestion extent in the low-duty-cycle network was determined not only by the number of packets in the network output queue,but also the destination of the packets.However,the traditional method with one-hop neighbors’ information cannot differentiate this kind of congestion.Therefore,combined with the dynamic switching mechanism,the DSRT proposed a congestion avoiding algorithm by classifying the packets in the queue.Through comprehensive experiments,the efficiency of routing discovering and congestion avoiding of the DSRT protocol is demonstrated,and the E2E delay is decreased by at least 200% when the traffic was high.